Keterampilan Membaca Berbasis Strategi Metakognitif pada Mahasiswa Perbankan dan Keuangan Politeknik Negeri Medan - Budi Indra Syahdewa; Siti Asnida Nofianna (Journal on Education, 2024)
This research aims to determine English reading skills through metacognitive strategies. This research method uses descriptive and qualitative methods. Data in the form of English learning results in tertiary institutions. Research data analysis uses data reduction, data presentation, and drawing data conclusions. The results of this research show that authentic assessment is appropriate to use for English reading skills because it can measure individual reading performance and development. Besides that, the use of metacognitive strategies can be a clear link between students' English reading abilities and the development of their abilities. Second, an authentic assessment pattern that is suitable for students, namely prioritizing learner characteristics, meaning that each individual assessment is different from other individuals because it is based on performance or self-mastery in reading skills.